2015
DOI: 10.1155/2015/976068
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Atrazine on the Development of Neural System of Zebrafish,Danio rerio

Abstract: By comparative analysis of histomorphology and AChE activity, the changes of physiological and biochemical parameters were determined in zebrafish embryos and larvae dealt with atrazine (ATR) at different concentrations (0.0001, 0.001, 0.01, 0.1, and 1 mg/L). This study showed that the development of the sarcomere and the arrangement of white muscle myofibers were affected by ATR significantly and the length of sarcomere shortened. Further analysis of the results showed that the AChE activity in juvenile fish … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…All four studies had null findings. Although there are no epidemiological studies of atrazine and eye defects, animal studies have reported abnormal eye development with exposure to atrazine ( Scahill 2008 ; Wang et al. 2015 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All four studies had null findings. Although there are no epidemiological studies of atrazine and eye defects, animal studies have reported abnormal eye development with exposure to atrazine ( Scahill 2008 ; Wang et al. 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…All four studies had null findings. Although there are no epidemiological studies of atrazine and eye defects, animal studies have reported abnormal eye development with exposure to atrazine (Scahill 2008;Wang et al 2015). PAX6 is important for glucose metabolism, and disruption of PAX6 expression increases the risk of diabetes (Panneerselvam et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Atrazine is a commonly used herbicide that prevents the growth of broad leaf and grassy weeds and also impacts vertebrate development (Song et al, 2014; Wang et al, 2015; Wirbisky et al, 2016a). Although it has been banned by the European Union (Sass and Colangelo, 2006), atrazine is still widely used across the United States and countries in Asia on plants such as corn, sugarcane, cotton, and pineapple.…”
Section: Introductionmentioning
confidence: 99%
“…Chronic ATR exposure results in high accumulative levels in multiple organs and tissues [10-14]. It has been shown that ATR and its metabolites, known as environmental endocrine disruptors, affect the central nervous and reproductive systems [15-17]. In terms of its nervous system toxicity, ATR decreases the level of striatal dopamine (DA) and the number of tyrosine hydroxylase (TH)-positive dopaminergic neurons in rodents, resulting in pathology and behavior similar to that of a Parkinson’s disease (PD) model.…”
Section: Introductionmentioning
confidence: 99%